1,8-Dihidroksi-3,6-Ditiyooktan İçeren Metalli ve Metalsiz Ftalosiyanin Bileşiklerinin Sentezi ve Karakterizasyonu - Pişkin, Yasemin (My University, 2019)
Yapılan bu çalışmada sırasıyla 5,6-diklorobenzofuran-1,3-dion (I), 5,6-dikloroizoindolin-1,3-dion (II), 4,5-dikloroftalamid (III), 4,5-dikloroftalonitril (IV), 2,3,5,6,8,9-hekzahidrobenzo[b][1,4]diokso[7,10]ditiyosiklododesen-12,13-dikarbonitril (V) bileşikleri sentezlenmiştir. 2,3,5,6,8,9-hekzahidrobenzo[b][1,4]diokso[7,10]ditiyosiklododesen-12,13-dikarbonitril (V) bileşiğinin, DBU (1.8-diazabisiklo[5.4.0]undek-7-en) katalizörü ve DMEA çözücüsü ile reaksiyonu sonucu metalsiz ftalosiyanin (H2Pc) (1) sentezlenmiştir. 2,3,5,6,8,9-hekzahidrobenzo[b][1,4]diokso[7,10]ditiyosiklododesen-12,13-dikarbonitril (V) bileşiğinin daha sonra sırasıyla susuz metal tuzları (NiCl2, CuCl2, CoCl2 ve Zn(CH3COO)2) kullanılarak, DBU katalizörü, DMEA çözücüsü ile reaksiyon sonucunda nikel ftalosiyanin (NiPc) (2), bakır ftalosiyanin (CuPc), kobalt ftalosiyanin (CoPc) (4) ve çinko ftalosiyanin (ZnPc) (5) sentezlenerek başlangıç maddelerinin ve ftalosiyanin yapıları elementel analiz, FT-IR, UV-vis., 1H-NMR, TG/DTG ve DTA analiz verilerinden yararlanılarak yapıları aydınlatılmıştır.

In this study, the following comounds; 5,6-dichloroisobenzofuran-1,3-dione (I), 5,5,6-dichloroisoindoline-1,3-dione (II), 4,5-dichlorophthalamide (III), 4,5-dichloro phthalanitrile (IV), 2,3,5,6,8,9-hexzhydrobenzo[b][1,4]dioxo[7,10]dithiacyclodode cine-12,13-dicarbonitrile (V) compounds were synthesized. Metal-free phthalo- cyanine (H2Pc) (1) was synthesized by the reaction between 2,3,5,6,8,9-hexz hydrobenzo[b][1,4]dioxo[7,10]dithiacyclododecine-12,13-dicarbonitrile (V) and DMEA solvent with the DBU (1.8-diazabicyclo [5.4.0] undec-7-ene) catalyzer. In consequence of the reaction of 2,3,5,6,8,9-hexzhydrobenzo[b][1,4]dioxo [7,10]dithiacyclododecine-12,13-dicarbonitrile (V), in the presence of DBU, DMEA and anhydrous CuCl2, copper phthalocyanine (CuPc) (2) was synthesized. Then 2,3,5,6,8,9-hexzhydrobenzo[b][1,4]dioxo[7,10] dithiacyclododecine-12,13-dicarbo nitrile (V) compound gave the reactions with anhydrous metal salts (CuCl2, NiCl2, CoCl2, Zn(CH3COO)2 respectively with usage of DBU catalyzer and DMEA solvent in order to bring about nickel phthalocyanine (NiPc) (3), cobalt phthalocyanine (CoPc) (4) and zinc phthalocyanine (ZnPc) (5) in the sequence of given anhydrous metal salts. The synthesized molecules (I), (II), (1), (2), (3), (4) and (5) were gained to the scientific literature. The structures of synthesized starter compounds and phthalocyanine were illuminated with elemental analyze techniques like FT-IR, UV-vis., 1H-NMR, TGA and DTA.
1,8-Dihydroxy-3,6-Dithiaoctane Containing Metal and Metal-Free Phthalocyanines Compounds Synthesis and Spectroscopic Properties
Keywords: Kimya; Sübstitüe Ftalosiyaninler; Chemistry; Substituted Phthalocyanines